2022-RA-269-ESGO Primary malignant follicular lymphoma of the uterine cervix, two case reports. (20th October 2022) - Zarragoitia, Janire; Baulies, Sonia; Casas, Francesc Tresserra; Fabregas, Rafael; Fargas, Francesc
Abstract : Introduction/Background: The incidence of non-Hodgkin lymphomas in Spain is 10.8/100.000 women. The extranodal lymphomas account for the 15%, only 1% being originated in the genital tract. Their management, prognosis and treatment efficacy is controverted. Methodology: First case: a 36-year-old asymptomatic patient undergoes annual checkup. The pelvic ultrasound shows a 31x37 mm cervical mass with score 4 vascularization, confirmed by MRI. Cytology and HPV come up negative. A cervical biopsy with immunohistochemistry analysis is performed, with positive results for BCL2–6, CD20, CD23 and CD5. The PET-CT shows no signs of metastases nor pathologic lymph nodes. Second case: a 45-year-old asymptomatic patient undergoes annual checkup. The pelvic ultrasound shows a 48x36 mm cervical mass with score 4 vascularization, confirmed by MRI. Cytology and HPV come up negative. A cervical biopsy with immunohistochemistry analysis is performed, with positive results for BCL6 and CD20. The PET-CT shows a suspicious right iliac lymph node, but no signs of distal metastases. Results: In case n°1, due to the desire of future pregnancy the patient undergoes chemotherapy after fertility preservation, who is in remission at this moment. In case n°2, the patient undergoes total hysterectomy and periodic checkups, also in remission at this moment. Conclusion: Less than 1/175 extra nodal lymphomas are likely to originate in the genital tract, and it is important to make a differential diagnosis with cervical cancer because both entities can present as vaginal bleeding, dyspareunia, or cervical mass. Diagnosis can be challenging due to frequent negative results from cytology, so the biopsy and immunohistochemical analysis is essential.Further investigation is needed in regard of the best treatment for this type of extra nodal lymphomas. Nowadays, itconsists of neoadjuvant/adjuvant chemotherapy combined with surgery, reaching the complete response in 75% of cases and survival rates of up to 90% after 5 years, according to the latest studies.